Strategi Belajar Kelompok Kecil dalam Menghafal Al-Qur’an oleh Guru Pendidikan Agama Islam di SDN 28 Jujutan Sangir Solok Selatan - Noprijon, Noprijon; Ilham, Seprian (UNIVERSITAS SERAMBI MEKKAH, 2024)
The teaching of the Qur’an by the teachers of Islamic education is very important in the development of the mastery of the knowledge of the Qur'an of the most special children in the western sumatra because of the success of the use of the koran of children that is decreasing is determined by the strategy of the educators of the school as the applicant and transporting the results of the application of the prophetic Qur’an by Islamic educators this depends on how the teacher is educating his and his methods when the teacher and his staff are serious in educating the students. This is a small group learning strategy in the teaching of the Qur'an by the teacher of Islamic education in SDN 28 jujutan sangir solok south. While the limitation of this research problem is how teachers of the Islamic religion education in teaching remembering the Qur’an in the SDN 28.